A multiscale flexible pressure sensor based on nanovesicle-like hollow microspheres for micro-vibration detection in non-contact mode. Issue 12 (13th March 2019) - Li, Tie; Li, Lili; Bai, Yuanyuan; Cao, Yudong; Lu, Qifeng; Li, Yue; Xu, Gengzhao; Zhang, Ting
Abstract : Hierarchical nanovesicle-like hollow microspheres are employed to fabricate flexible pressure sensors for detecting micro-vibration signals in non-contacting mode. Abstract : To detect micro-vibration, flexible pressure sensors require that the sensing materials possess superior sensitivity in non-contact sensing mode. One type of matter, nanovesicles, has the characteristics of hollow spheres and crack junctions in a single body, and provides an exciting bionic idea to explore high-sensitivity sensing materials. Hence, in this study, novel hollow microspheres with a hierarchical nanovesicle-like architecture are designed, prepared via a controlled strategy of adjusting the surface energy, and employed to fabricate multiscale flexible pressure sensors that display a high response sensitivity of 11.3 kPa −1 and a low detection limit of 5.5 Pa with good stability for 2500 cycles. The working mechanism can be deduced as the synergistic effects from the stress concentration of microstructural patterns and the successive deformation of the nanovesicle-like structure, which is revealed by controlled experiments and finite element method simulations. The as-assembled flexible pressure sensor is used to detect the dynamic micro-vibration signals caused by fluid motion (water flow and airflow) and inelastic/elastic collision in non-contact mode, revealing good sensitivity, repeatability and stability. This work provides theoretical and experimental evidence for the development of hierarchical structure-based highly sensitive flexible sensors in the future.